Under the radar: policing non-violent domestic abuse in the US and UK. Issue 3 (2nd July 2016) - Robinson, Amanda L.; Pinchevsky, Gillian M.; Guthrie, Jennifer A.
ABSTRACT: Physical violence is but one of many tools that may be used to gain greater power within intimate relationships, yet the legal response has been critiqued for failing to recognise and respond to the full spectrum of abusive behaviours, such as coercive control. Using a sample of police officers from the United States (US) and the United Kingdom (UK), the current study utilises hypothetical vignettes to assess police officers' perceptions of domestic abuse, including those incidents that are not necessarily physically violent, but involve stalking and other coercive, controlling behaviours that are harmful and require intervention. Within- and between-country similarities and differences were analysed. Findings revealed that the majority of officers in both countries possessed a good level of understanding of domestic abuse and how they should respond to it – amidst and beyond the physical violence. However, our analysis of both quantitative and qualitative data also showed that the use of physical violence is at the forefront of many officers' expectations about domestic abuse, and that when physical violence is absent, the police response is less proactive. Our study finds some support for the idea that non-physical abuse does go "under the radar" to some extent for some officers, and that this is more the case for American officers than their British counterparts. Findings are discussed in terms of context of the research sites and implications for policy, practice and future research.